All Days 2012
DOI: 10.2118/150548-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Drilling Fluid Content on Magnetic Shielding of Downhole Compasses in MWDs

Abstract: The magnetic property of the drilling fluid is one of the substantial error sources for the determination of azimuth while drilling deviated wells. These errors may be in the range of 1-200m if drilling long, deviated intermediate sections. Therefore, these effects represent a significant cost to be mitigated. The error becomes even more pronounced if drilling occurs in arctic regions close to the magnetic North pole. Added clays, weight materials and the tubular wear are anticipated to distort the geomagnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Laboratory experiments confirmed that the magnetic field of the Earth was attenuated when a three-axis probe was lowered into a field-used drilling fluid containing magnetic waste particles [4]. This theory was also confirmed by Tellefsen et al (2012) [5] through their work. The problem is still present today.…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…Laboratory experiments confirmed that the magnetic field of the Earth was attenuated when a three-axis probe was lowered into a field-used drilling fluid containing magnetic waste particles [4]. This theory was also confirmed by Tellefsen et al (2012) [5] through their work. The problem is still present today.…”
Section: Introductionmentioning
confidence: 78%
“…At approximately 6000 seconds, the shielding effect reaches its maximum before it starts dropping again towards its initial value. This effect is anticipated to be cause by small from the work was that magnetic contaminants taken from a ditch magnet showed a significant effect on magnetic shielding [5].…”
Section: Shielding Effect From Magnetic Contaminated Drilling Fluid Omentioning
confidence: 92%
See 3 more Smart Citations